2013
DOI: 10.1095/biolreprod.112.105460
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Lgals9 Splice Variant Expression at the Fetal-Maternal Interface: Implications in Normal and Pathological Human Pregnancy1

Abstract: Disruption of fetal-maternal tolerance mechanisms can contribute to pregnancy complications, including spontaneous abortion. Galectin-9 (LGALS9), a tandem repeat lectin associated with immune modulation, is expressed in the endometrium during the mid and late secretory phases and in decidua during human early pregnancy. However, the role of LGALS9 during pregnancy remains poorly understood. We used real-time PCR and immunohistochemical staining to analyze the expression of Lgals9/LGALS9 during mouse gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…Similarly, Wu et al found that women with recurrent spontaneous abortions (defined as 3 or more pregnancy losses) had lower levels of galectin‐9 in peripheral blood compared to the normal pregnancy group. In addition, placentas from fetal resorption models had lower mRNA quantities of galectin‐9 compared to normal placenta . Thus, further studies are necessary to determine whether this could serve as a biomarker to assess the health of the pregnancy or whether exogenous galectin‐9 might be used to prevent pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wu et al found that women with recurrent spontaneous abortions (defined as 3 or more pregnancy losses) had lower levels of galectin‐9 in peripheral blood compared to the normal pregnancy group. In addition, placentas from fetal resorption models had lower mRNA quantities of galectin‐9 compared to normal placenta . Thus, further studies are necessary to determine whether this could serve as a biomarker to assess the health of the pregnancy or whether exogenous galectin‐9 might be used to prevent pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…These splice variants encode protein isoforms that vary in the length of the linker region between the two CRD domains which affects multimer formation and valency [38], [39]. Previous data suggest that the different galectin-9 isoforms have a diverging role in tumor cells, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…they differently affect the adhesion of cells to the ECM and to the endothelium [40]. In general, altered galectin-9 expression has been linked to abnormal cell adhesion, growth and migration [39]. Others have described that galectin-9 can influence cell survival as well as homo- and heterotypic cell aggregation [9], [34], [40]–[43].…”
Section: Discussionmentioning
confidence: 99%
“…As for gal‐9, this lectin is substantially upregulated in human decidua compared to proliferative endometrium . We recently showed the expression of at least six gal‐9 isoforms in decidual tissue, and that the Lgals9 D5 variant can selectively suppress IFN‐γ production by uterine NK cells . Finally, expression of gal‐9 has also been reported in the epitheliochorial placenta, though at lower levels than in the decidual compartment …”
Section: Introductionmentioning
confidence: 96%
“…While some galectins contain one CRD and are biologically active as either homodimers (e.g., galectin‐1) or oligomers that aggregate through their non‐lectin domain (galectin‐3); other galectins contain two CRDs connected by a short linker peptide (e.g., galectin‐9) . Several members of this family play an active role in pregnancy maintenance by regulating trophoblast cell growth and differentiation, angiogenesis and inflammation throughout gestation . Within this family, galectin‐1 (gal‐1), gal‐3 and gal‐9 are of particular interest as they are highly expressed at the maternal–fetal interface .…”
Section: Introductionmentioning
confidence: 99%